Plasma cross-gestational sphingolipidomic analyses reveal potential first trimester biomarkers of preeclampsia. - Aneta Dobierzewska; Sony Soman; Sebastian E Illanes; Andrew J Morris (PLoS ONE, 2017)
Preeclampsia (PE) is a gestational disorder, manifested in the second half of pregnancy by maternal hypertension, proteinuria and generalized edema. PE is a major cause of maternal and fetal morbidity and mortality, accounting for nearly 40% of all premature births worldwide. Bioactive sphingolipids are emerging as key molecules involved in etiopathogenesis of PE, characterized by maternal angiogenic imbalance and symptoms of metabolic syndrome. The aim of this study was to compare the cross-gestational profile of circulating bioactive sphingolipids in maternal plasma from preeclamptic (PE) versus normotensive control (CTL) subjects with the goal of identifying sphingolipids as candidate first trimester biomarkers of PE for early prediction of the disease.A prospective cohort of patients was sampled at the first, second and third trimester of pregnancy for each patient (11-14, 22-24, and 32-36 weeks´ gestation). A retrospective stratified study design was used to quantify different classes of sphingolipids in maternal plasma. We used a reverse-phase high-performance liquid chromatography-tandem mass spectrometry (HPLC-ESI-MS/MS) approach for determining different sphingolipid molecular species (sphingosine-1-phosphate (S1P), dihydro-sphingosine-1-phosphate (DH-S1P), sphingomyelins (SM) and ceramides (Cer)) in cross-gestational samples of human plasma from PE (n = 7, 21 plasma samples across pregnancy) and CTL (n = 7, 21 plasma samples across pregnancy) patients.Plasma levels of angiogenic S1P did not change significantly in control and in preeclamptic patients´ group across gestation. DH-S1P was significantly decreased in second trimester plasma of PE patients in comparison to their first trimester, which could contribute to reduced endothelial barrier observed in PE. The major ceramide species (Cer 16:0 and Cer 24:0) tended to be up-regulated in plasma of control and PE subjects across gestation. The levels of a less abundant plasma ceramide species (Cer 14:0) were significantly lower in first trimester plasma of PE patients when compared with their gestational-matched control samples (p = 0.009). Major plasma sphingomyelin species (SM 16:0, SM 18:1 and SM 24:0) tended to be higher in control pregnancies across gestation. However, in PE patients, SM 16:0, SM 18:0 and SM 18:1 showed significant up-regulation across gestation, pointing to atherogenic properties of the sphingomyelins and particularly the potential contribution of SM 18:0 to the disease development. In addition, two major sphingomyelins, SM 16:0 and SM 18:0, were significantly lower in first trimester plasma of PE patients versus first trimester samples of respective controls (p = 0.007 and p = 0.002, respectively).Cross-gestational analysis of maternal plasma of preeclamptic and normotensive women identifies differences in the biochemical profile of major sphingolipids (DH-S1P, sphingomyelins and ceramides) between these two groups. In addition, first trimester maternal plasma sphingolipids (Cer 14:0, SM 16:0 and SM 18:0) may serve in the future as early biomarkers of PE occurrence and development.